(3TQM JTQjM GdCadGcs - (3aVd Gddg GdKGfi Hf eMeO GdTQja GdcGTGfis; (3eMeO Hf GdMSf Hf Rjf GdOjf GdehShj GdYGedj , GHf GdTgjO GdKGfj,J (B1030 (3g` s
(3ChdgG (B:s
(3GdefI ddg hHYO , jbhd gPG eG TQMJ GdcJGH GdehShe HJTQjM GdCadGc hgh bO COQL ajg cKjQkG ef GdfcGJ hdGSjeG af GdgjFI s
(3BNQgG (B:s
(3GdbHdI Edi NdGa LgI GdXd gPG eG ZadJ Yfg YhGFb GdReGf hGdMeO ddg gPG eG JjSQ di ai TQM gPG GdcJGH s
(3CJe TQMg SfI (B1072s
(3HBNQgG SeGY JGQjNg eWehSs
(3HgG CKGQ WeSs
(3HgG CTcGd s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs